2014
DOI: 10.1186/1471-2415-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Normal-tension glaucoma and obstructive sleep apnea syndrome: a prospective study

Abstract: BackgroundToday, identified risk factors for normal-tension glaucoma (NTG) include abnormal ocular blood flow, abnormal blood coagulation, systemic hypotension, ischemic vascular disorders, and autoimmune diseases. However, pathogenesis of the condition remains unclear. On the other hand, there are also a few studies suggesting that the obstructive sleep apnea syndrome (OSAS) may compromise optic nerve head perfusion and cause glaucomatous optic neuropathy by creating transient hypoxemia and increasing vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 17 publications
(16 reference statements)
2
33
2
4
Order By: Relevance
“…This is also supported by a relative risk of 3.34 to have OSA in patients with NTG compared with systemic risk factors-matched subjects. 38 NAION was the least frequently observed ED. Although the underlying pathophysiological mechanisms of NAION have not yet been fully elucidated, it has been hypothesised that there is a circulatory insufficiency within the optic nerve head during a nocturnal non-dipping blood pressure Open Access profile promoted by OSA.…”
Section: Discussionmentioning
confidence: 98%
“…This is also supported by a relative risk of 3.34 to have OSA in patients with NTG compared with systemic risk factors-matched subjects. 38 NAION was the least frequently observed ED. Although the underlying pathophysiological mechanisms of NAION have not yet been fully elucidated, it has been hypothesised that there is a circulatory insufficiency within the optic nerve head during a nocturnal non-dipping blood pressure Open Access profile promoted by OSA.…”
Section: Discussionmentioning
confidence: 98%
“…68,69 Studies have reported that people with OSA tend to have increased IOP values, possibly related to increased body mass index and RNFL thinning with visual field defect. The proposed pathogenesis of OSA in NTG seems to be multifactorial, mainly mechanical and vascular factors.…”
Section: Systemic Diseasesmentioning
confidence: 98%
“…[34] This causes decrease in the arterial oxygen (O 2 ) saturation and a rise in the carbon dioxide saturation during sleep[5] and results in transient hypoxia and increased vascular resistance in body tissues. In case of ocular tissues, this results in a reduction of ocular perfusion pressure and decreased oxygenation to the optic nerve which eventually leads to glaucomatous optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In case of ocular tissues, this results in a reduction of ocular perfusion pressure and decreased oxygenation to the optic nerve which eventually leads to glaucomatous optic neuropathy. [5] It shows specific symptoms and signs such as excessive daytime sleepiness or fatigue and obesity. The prevalence of OSA in community screening is 2%-6% for moderate and above and 14% for mild form.…”
Section: Introductionmentioning
confidence: 99%